2016
DOI: 10.3136/nskkk.63.306
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Effects of Oral Administration of GABA in Humans

Abstract: We investigated the effects of γ -aminobutyric acid (GABA) on facial skin conditions in humans. A placebocontrolled, double-blind 8-week study of GABA (100 mg/day) was conducted on 36 women with dry skin, fatigue and sleep disorder. After 8 weeks, skin elasticity of the cheek was significantly higher in the GABA group than in the placebo group. Although improvement in sleep quality was observed in both groups, there was no significant difference between groups. These results suggest that ingestion of GABA incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…13) We previously reported that the administration of GABA improved AD-like skin lesions in NC/Nga mice by adjusting the Th1/Th2 balance. 14) Furthermore, a placebo-controlled, double-blind study indicated that oral administration of GABA significantly increased the skin elasticity 15) however, its regulatory mechanism is not understood. In this study, we therefore investigate the effects of GABA on the expression of type I collagen (COL1A1 and COL1A2) and matrix metalloproteinase-1 (MMP-1) in normal human dermal fibroblasts (NHDFs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13) We previously reported that the administration of GABA improved AD-like skin lesions in NC/Nga mice by adjusting the Th1/Th2 balance. 14) Furthermore, a placebo-controlled, double-blind study indicated that oral administration of GABA significantly increased the skin elasticity 15) however, its regulatory mechanism is not understood. In this study, we therefore investigate the effects of GABA on the expression of type I collagen (COL1A1 and COL1A2) and matrix metalloproteinase-1 (MMP-1) in normal human dermal fibroblasts (NHDFs).…”
mentioning
confidence: 99%
“…23) We also reported that oral administration of GABA significantly increased the skin elasticity in human study. 15) In addition, GABA Table 1. Primer sequences.…”
mentioning
confidence: 99%
“…16) In trials involving healthy human subjects, GABA was rapidly absorbed and reached a peak concentration in the plasma 1 h after oral administration, resulting in significantly increased circulating insulin levels to improve diabetes. 17) We also previously reported that oral administration of biosynthesized GABA significantly increased skin elasticity, 6) and treatment with biosynthesized GABA significantly upregulated the expression of type I collagen and downregulated MMP-1 expression in HDFs. 7) In this study, we further examined whether GABA regulates elastic fiber formation in HDFs.…”
Section: Discussionmentioning
confidence: 77%
“…5) Furthermore, a placebo-controlled, double-blind study indicated that the oral administration of biosynthesized GABA significantly increased skin elasticity. 6) Biosynthesized GABA administration upregulated the expression of type I collagen and downregulated matrix metalloproteinase (MMP)-1 expression in HDFs in vitro. 7) However, detailed knowledge of its regulatory mechanism is lacking, especially regarding the control of elastic fiber formation.…”
mentioning
confidence: 99%
“…Further, a placebo controlled, double-blind 8-week study involving 36 women with dry skin, fatigue and sleep disorder that ingesting 100 mg GABA/day increased skin elasticity of the cheek (Hokazono et al 2016). Such skin improvements are associated with increased GH levels.…”
Section: Discussionmentioning
confidence: 99%